Effective Disaster Prevention or Mitigation by Examining the Significance of Disaster Resilience - 이재은; 김서용; Gajendra Sharma; Muhammad Azam (Crisisonomy, 2019)
The purpose of this study is to suggest some implications for effective disaster prevention or mitigation through examining the significance of disaster resilience. As a result, some major implications of this study are as follows; serious and in-depth cause analysis should be conducted to mitigate or minimize the likelihood of recurrence of the same type of disaster from past disasters; the cooperation between the disaster management institutions should be practically established; public officials should personally engage in responsible actions to prevent disasters and mitigate damage; it is necessary to increase the level of cooperation and information exchange between the central and local governments responsible for disaster management, public officials with disaster experience and public officials without disaster experience, and public sector and private sector; a depth academic research should be conducted to analyze the impact of disaster on individuals, households and society, etc.
Keywords: disaster resilience; prevention; mitigation; disaster management